2017
DOI: 10.3389/fmed.2017.00096
|View full text |Cite
|
Sign up to set email alerts
|

Factors Promoting Development of Fibrosis in Crohn’s Disease

Abstract: The concepts on the pathophysiology of intestinal fibrosis in Crohn’s disease (CD) have changed in recent years. Some years ago fibrosis was regarded to be a consequence of long-standing inflammation with subsequent destruction of the gut wall matrix followed by scar formation and collagen deposition. Fibrosis in CD patients appeared to be an irreversible process that could hardly be influenced. Therefore, the main target in CD therapy was to control inflammation to avoid fibrosis development. Many of these as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
1
16
1
1
Order By: Relevance
“…Intestinal fibrosis associated to Crohn's disease is characterized by an intense submucosal and subserosal ECM deposition. 2,24 Several animal models of intestinal fibrosis have been proposed 25 and we consider that the heterotopic transplant model of fibrosis used in the present study reproduce some features of CD fibrosis, such as transmural inflammation and ECM deposition. 26,27 We observed an important submucosal and subserosal collagen accumulation and high levels of fibrosis markers associated with an increased expression of SUCNR1 in WT grafts 7 days after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal fibrosis associated to Crohn's disease is characterized by an intense submucosal and subserosal ECM deposition. 2,24 Several animal models of intestinal fibrosis have been proposed 25 and we consider that the heterotopic transplant model of fibrosis used in the present study reproduce some features of CD fibrosis, such as transmural inflammation and ECM deposition. 26,27 We observed an important submucosal and subserosal collagen accumulation and high levels of fibrosis markers associated with an increased expression of SUCNR1 in WT grafts 7 days after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…49 Rogler and Hausmann 50 posited that new animal models for intestinal fibrosis may provide insight into mechanisms of disease and identify specific therapies for fibrosis in people with CD. 50 Using the SHIP −/− mouse, we have found that targeting PI3Kp110δ activity can reduce CD-like intestinal fibrosis. A new drug targeting PI3Kp110δ activity, idelalisib, has recently been developed and licensed for use in the United States and European Union for the treatment of B cell neoplasms.…”
Section: Discussionmentioning
confidence: 98%
“…An allele that could lead to overexpression of the main profibrotic mediator, TGF-β, has been identified [8], which could lead to more rapid development of fibrosis and strictures. Another explanation could be that inflammation and fibrosis are initially linked in the pathogenesis, but later become two independent processes [9]. is might explain why fibrosis cannot be reversed by anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%